Efficacy of Probiotics on Nutrient Intake and Egg Weight in Japanese Quail (Coturnix coturnix japonica) - Kirana, Amelia Lintang Putri; Lovela, Aprinda Ratna; Lokapirnasari, Widya Paramita; Al-Arif, Mohammad Anam; Hidanah, Sri; Warsito, Sunaryo Hadi; Ardianto, Ardianto (Jurnal Medik Veteriner, 2024)
This study aimed to determine the efficacy of lactic acid bacteria probiotics containing Lactobacillus acidophilus and Lactococcus lactis on nutrient consumption and egg weight of Japanese quail. A total of 120 females Japanese quails comprised four treatments and six replications. T0, T1, T2, and T3 treatment groups were administered L. acidophilus and L. lactis with concentrations of 0, 1, 2, and 3 mL/liter of drinking water. Consumption data were collected weekly, and egg weight data were collected daily during treatment. The data obtained were then analyzed statistically using analysis of variance (ANOVA) and continued with the Duncan multiple range test (p < 0.05). The results of this study showed that probiotics in drinking water reported significant differences (p < 0.05) compared between treatments (T1, T2, and T3) to reduce nutrient intake of organic matter, crude protein, crude fat, crude fiber and increase egg weight of quail. It can be concluded that the combination of L. acidophilus and L. lactis can reduce nutrient consumption but can increase the egg weight of Japanese quail.